The introvert's complete career guide : from landing a job, to surviving, thriving, and moving on up - Finkle, Jane (Career Press, 2019)
"This handbook demonstrates how to use your introverted qualities to their best advantage, then add a few extroverted skills to round out a forceful combination for ultimate career success. Includes keys to navigating each stage of professional development--from self-assessment and job search to survival in a new position and career advancement"--